Risk is fisk? - Alex Stomper; Marie-Louise Vierø (Queen's University, Department of Economics, 2017)
We analyze the relation between firms' exposure to exogenous business risk and their financing choices, based on a sample of firms for which we can measure such exposure. The results show that firms more exposed to exogenous risk use less debt financing. We also analyze the relation between the volatility of the firms' returns-on-assets, and their use of debt financing. The result is the opposite of that obtained for exogenous risk: we find a positive relationship between debt financing and the risk of firms. Overall, our results show that different types of risk are associated with different financing choices. While exogenous risk causes firms to use less debt financing, debt financing causes firms to take risk endogenously. This result explains contradictory findings regarding the relation between risk and debt financing in the prior literature.
Keywords: 330